Metamorphoses: Transformations as a discourse of development and a form of life - Zheleznyak, Olga (project baikal, 2024)
“Transformations” as the essence of Ovidian metamorphoses are one of the forms of life, the purpose and potentiality of the world’s development. Ambivalence often serves as a kind of stimulus for the emergence of metamorphoses or their basis. The ambivalent potential of the world provokes the expansion of transformations/metamorphoses. “Transformations” represent current trends in architecture and design, including transformations of objects and environments; the emergence of peculiar “architectural centaurs” and hybrid environments; imitations and mimicking facades/environments.